Knowledge on contraception and safe sex among college students in Shanghai: a network-based cross-sectional survey - Wen-rong XIA; Chun-lin ZHAN; Hai-wang ZHOU (Editorial Office of Chinese Journal of Public Health, 2022)
Objective To examine the knowledge on contraception and safe sex among college students in Shanghai for providing evidences to promote reproductive health of college students in China. MethodsAn onsite/online network-based anonymous survey was conducted among 16 235 students of various degrees in 62 colleges and universities during June - November, 2019. A self-designed questionnaire on knowledge, attitude and behaviors about safe sex and contraception was used in the survey. ResultsOf the 14 612 students (4 829 males and 9 783 females averagely aged 21.63 years) with valid replies, 24.93% reported ever having sexual behavior. Among the respondents with sex experiences, 66.80% reported adopting contraceptive measures every time but 3.46% stated never taking contraceptive measures when having sex; and unintended pregnancy was reported by 7.24% of the respondents. For all the respondents in terms of contraceptive measures, the knowledge rate was 82.90% for condom, 26.51% for spermicide, 17.72% for contraceptive injections, and 15.30% for contraceptive subcutaneous implant. The reported knowledge about induced abortion was higher among the female respondents than among the males. There were 47.16% of all the respondents not having sufficient knowledge about sexually transmitted disease and AIDS and the ratio was lower among male respondents than among the females. ConclusionIn colleges or universities of Shanghai, the students are open in their attitude about sex and active in sexual relationships but the students are lack of knowledge about contraception and avoidance of unintended pregnancy. The results suggest that specific education on safe sex and a better reproductive health services should be promoted among the students.